Complexity-based local diagnostic reference levels (DRLs) for standard endovascular aneurysm repair (EVAR) procedures. (May 2020) - Tzanis, Eleftherios; Ioannou, Christos V.; Tsetis, Dimitrios; Lioudaki, Stella; Matthaiou, Nikolas; Damilakis, John
Highlights: Complexity-based DRLs must be defined in interventional radiology. Complexity-based local DRLs for standard EVAR procedures are presented. Increased procedural complexity leads to higher DRL values. Indices for the quantification of procedural complexity in EVAR are proposed. Abstract: Purpose: The aim of this study was to establish complexity-based local diagnostic reference levels (DRLs) for standard endovascular aneurysm repair (EVAR) procedures. Methods: Dosimetric data for 73 consecutive patients were collected prospectively. All procedures were performed on a Siemens Axiom Artis FA angiographic unit (Siemens, Erlangen, Germany). Fluoroscopy time (FT), dose area product (DAP), air kerma ( K a . r ) at reference point as well as patient's age, height and weight were recorded for each procedure. Moreover, the complexity level of each procedure was evaluated. Spearman rank correlation tests were used to evaluate the degree of association between variables. Results: 2nd quartiles of DAP for low, medium and high complexity standard EVAR procedures were 144.2 Gy c m 2, 160.1 Gy c m 2 and 189.5 Gy c m 2 respectively. The median DAP of the full sample was 153.2 Gy c m 2 . Statistical analysis showed a strong correlation between BMI and DAP (r = 0.68, p-value < 0.0001) and a moderate correlation between BMI and K a . r (r = 0.52, p-value < 0.0001). Furthermore, a strong correlation was found between K a . r and FT (r = 0.76, p-value < 0.0001) and a moderate correlation was found between DAP and FT (r = 0.57, p-value < 0.0001). Conclusion: The complexity of an EVAR procedure is associated with the total burden of radiation. Establishment of complexity-based DRLs for interventional radiology procedures can contribute to the radiation protection of patients and staff.